Musik Ritual Bebalai dalam Upacara Adat Pesta Laut Bontang Kuala di Bontang Kalimantan Timur - Hirda Yulinalmi; Asril Gunawan; Zamrud Whidas Pratama (Jurnal Mebang: Kajian Budaya Musik dan Pendidikan Musik, 2023)
This research aims to describe the presentation form and function of Bebalai music in the traditional ceremony of "Pesta Laut" Bontang Kuala. The "Pesta Laut" ceremony is a ritual for the indigenous people of Bontang Kuala that is still preserved and held every year from November to December. The "Pesta Laut" ceremony has meaning as a form of gratitude to God Almighty to be kept away from danger and various kinds of diseases. The Pesta Laut ceremony is divided into seven processions: (1) mencera buluh; (2) balai pompong; (3) melabuh perahu; (4) menjamu karang; (5) ance; (6) pagar mayang; and (7) balai puncak. The "Pesta Laut" ceremony also involves the arts, which include Bebalai music. The theories used are ceremony theory by Koentjaraningrat and function theory by R.M. Soedarsono. This research uses a descriptive method with a qualitative approach. The result of this research is that along with the times, the "Pesta Laut" ceremony has experienced a shift by adjusting to the environmental conditions of the community. It can be seen from the traditional rituals that were once highly sacred by the people of Bontang Kuala but are now carried out as ceremonial events.